Values Of Religious-Multiculturalism Education In The Qatar 2022 World Cup Football Event - Sholehuddin, Moh; Hosen, Hosen; Mukit, Abdul; Gafur, Abdul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
In various aspects of life, such as the gentle power of Qatar in publishing Islamic values to the international world in the form of religious values and multiculturalism. Qatar 2022 World Cup is one of the most different hosts of all time. Qatar's attitude shows that Islam is a religion that calls for good things for humans. This study uses a qualitative method with a library research and journal approach related to Religious-Multiculturalism Values in the 2022 Qatar World Cup Football Event. This research shows that Islam is not a religion that does not respect human differences, it also shows that Islam is an exclusive teaching. which is intended for followers who were born to Muslim parents, but Islam can also be learned and known by non-Muslims.